The Effect of Social Media Specialists on Operational Effectiveness and Increased Insight at the Company PT. Aaron Innovation Indonesia - Nevari, Shintya Rizky; Hariyana, Nanik (SINTA Journal (Science, Technology, and Agricultural), 2024)
The role of a Social Media Specialist (SMS) in a company is becoming increasingly crucial in this digital era. This research aims to analyze the impact of the presence of an SMS on operational effectiveness and the enhancement of company insights. Using both qualitative and quantitative methods, this study explores how the expertise and strategies applied by an SMS can improve operational efficiency and provide deep insights for the company. The findings indicate that an SMS significantly contributes to enhancing customer interaction and engagement through social media platforms, which in turn improves the company's communication and operational flow. Additionally, the social media data analysis conducted by an SMS provides valuable insights into consumer behavior and preferences, which can be used to develop more effective and targeted marketing strategies. The implication of this research is that PT. Aaron Innovation Indonesia needs to invest resources in the development of SMS skills and the integration of social media functions with company operations to achieve competitive advantage in an increasingly dynamic market. This study highlights the importance of the SMS role not only in facilitating more efficient communication but also in providing reliable data for strategic decision-making.